Sex differences in clinical presentation of systemic lupus erythematosus - Ramírez Sepúlveda, Jorge I. (Biol Sex Differ, 2019)
OBJECTIVE: Systemic lupus erythematosus (SLE) predominantly affects women, but previous studies suggest that men with SLE present a more severe disease phenotype. In this study, we investigated a large and well-characterized patient group with the aim of identifying sex differences in disease manifestations, with a special focus on renal involvement. METHODS: We studied a Swedish multi-center SLE cohort including 1226 patients (1060 women and 166 men) with a mean follow-up time of 15.8 ± 13.4 years. Demographic data, disease manifestations including ACR criteria, serology and renal histopathology were investigated. Renal outcome and mortality were analyzed in subcohorts. RESULTS: Female SLE patients presented more often with malar rash (p < 0.0001), photosensitivity (p < 0.0001), oral ulcers (p = 0.01), and arthritis (p = 0.007). Male patients on the other hand presented more often with serositis (p = 0.0003), renal disorder (p < 0.0001), and immunologic disorder (p = 0.04) by the ACR definitions. With regard to renal involvement, women were diagnosed with nephritis at an earlier age (p = 0.006), while men with SLE had an overall higher risk for progression into end-stage renal disease (ESRD) with a hazard ratio (HR) of 5.1 (95% CI, 2.1–12.5). The mortality rate among men with SLE and nephritis compared with women was HR 1.7 (95% CI, 0.8–3.8). CONCLUSION: SLE shows significant sex-specific features, whereby men are affected by a more severe disease with regard to both renal and extra-renal manifestations. Additionally, men are at a higher risk of developing ESRD which may require an increased awareness and monitoring in clinical practice.